On The Government of the Living - Foucault, M. author. aut Link
XVIII, 365 p.
Keywords: With these lectures Foucault inaugurates his investigations of truth-telling in the ethical domain of practices of techniques of the self. How and why, he asks, does the government of men require those subject to power to be subjects who must tell the truth about themselves? .